Faktor-faktor yang mempengaruhi Tax Avoidance: Sales Growth, Profitabilitas dan CSR - Juli Ratnawati; Vita Resti Wulidasani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This studies is performed to observe sales increase,profitability,and corporate social duty as variables that affect tax avoidance practices. The populace of this studies is the mining area which is listed on Indonesia stock market in period of 2019-2021. The usage of a purposive sampling approach. The secondary facts obtained from Indonesia stock market and economic record of every employer that applicable with purposive sampling standards . Speculation testing makes use of multiple linear regression evaluation with the help of SPSS software program. The consequences of this studies display that sales increase has an effect on Tax Avoidance. Profitability does no longer affect Tax Avoidance. CSR impacts Tax Avoidance.